Characterization of work-related cancer in the territory of Cerest Registro, SP: descriptive study, 2015-2021 (Research, Society and Development, 2022)
The objective of this research was to characterize work-related cancers reported by health units in the area covered by the Centro de Referência em Saúde do Trabalhador - CEREST Registro/SP, from 2015 to 2021. This is an epidemiological and descriptive study. cross-sectional study performed with secondary cancer data related to the work of the Information System on Notifiable Diseases of the CEREST Registro/SP. The prevalence and association of sociodemographic and occupational variables were evaluated, identifying the epidemiological link between occupational activity and the type of cancer diagnosed. Pearson's chi-square test (χ2) was used considering categorical data to assess the sociodemographic variables associated with the ICD-10. Results: The most prevalent diseases were cancers occurring in the oral cavity and digestive tract (71.43%) in workers in the "agricultural, forestry and fishing" group, especially in males, which denotes 6.8 times more chances of getting cancer in this region (OR 6.8, 95% CI: 2.1-21.6), and 73.33% of this group was exposed to substances used in pest control. “production of industrial goods and services”the greatest exposure factors were asbestos, silica and dust (83.33%) affected by 12 different types of cancer. Conclusion: Evidence was recorded on exposure to risk factors with pesticides and the agricultural, forestry and fishing workers, with tumors in the oropharyngeal cavity and digestive tract predominating, suggesting an epidemiological link with work.